(untitled) - Gould, Richard A. (Cambridge,New York, 2000)
Maritime archaeology deals with shipwrecks and is carried out by divers rather than diggers. But this is by no means a marginal branch of archaeology. It embraces maritime history, analyzing changes in ship-building, navigation, reconstructing the infrastructure of waterborne commerce, and offers fresh perspectives on the cultures and societies that produced the ships and sailors. Drawing on detailed and recent case studies, Richard Gould provides an up-to-date review of the field and a clear exposition of new developments in undersea technologies. He also argues for the careful management of underwater cultural resources.
Keywords: Underwater archaeology,Shipwrecks,Ships,Khảo cổ dưới mặt nước,Sự đắm tàu,Thuyền; History,Lịch sử